A Case-Control Study of Photodynamic Therapy Combined with Thymosin in the Treatment of Condyloma Acuminatum in Anal Canal. (12th March 2022) - Wang, Xia Qing; Hu, Yi; Hong, Ke
Abstract : A case-control study is performed in this paper to explore various possible effects and clinical value of the photodynamic therapy combined with thymosin for the treatment process of the condyloma acuminatum (CA) in the anal canal. For this purpose, a hundred (100) patients specifically with CA in the anal canal who were regularly treated in the hospital from February 2019 to April 2021 were recruited. The first group, that is, the control group, was treated with thymosin, whereas photodynamic therapy combined with thymosin was used as a treatment for the study group. The curative effect, clinical index, LTN, SP, TGF- β 1, TNF- α, CD3+, CD4+, CD8+, and the adverse reactions of incidence were compared between these groups. Moreover, 27 cases were observed to be obviously effective, 22 were observed to be effective, and a single case was observed to be ineffective. Thus, 98% is the total effective rate where a single case relapses. Likewise, in the control group, 15 cases were observed to be obviously effective, 28 effective, and 13 ineffective. Thus, 86% is the total rate of effectiveness where thirteen (13) cases relapse. We have observed that the study group has a higher rate of effectiveness than the control group and the rate of recurrence of the former group was slightly lower than that of the latter group, that is, the control group (P < 0.05). In addition, the time of symptom improvement, the amount of bleeding, the disappearance time of bloody stool, and the time of the first recurrence of the study group were observed to be lower than those of the control group (P < 0.05). In levels of LTN and SP, we have observed no or zero significant differences between these groups before treatment. However, LTN's levels of both groups increased after the treatment, and SP's level decreased. LTN's level of the study group was observed to be higher than that of the other group, and SP's level in the former group was lower than that in the latter group. Zero significant differences were observed in the TGF- β 1 and TNF- α 's levels between these groups before treatment, but the level of TGF- β 1 and TNF- α has increased and decreased, respectively, in both groups specifically after treatment. The level of TGF- β 1 in the former group was observed to be slightly higher than that in the latter group, that is, the control group, while TNF- α 's level in the study group was lower than that in the control group. We have not observed any significant difference in CD4+, CD3+, and CD8+ levels between these groups before treatment. However, after treatment, CD3+ and CD4+ levels increased, and the levels of CD8+ decreased in both groups, while CD3+ and CD4+ levels in the former group were evident to be higher than those in the latter group and the level of the CD8+ in the study group was observed to be lower than that in the control group. Finally, we compared the adverse reactions of incidence between these groups. There were 4 cases of tingling sensation and 1 case of redness and swelling in the group study along with a total incidence of 10%. There were 5 cases of tingling sensation and 2 cases of redness and swelling in the control group along with a total incidence of 14%. The incidence of adverse reactions in the study group was observed to be slightly lower than that in the control group, but a significant difference was not observed between these groups ( χ 2 = 0.378; P > 0.05).